PENGEMBANGAN E-MODUL BERBASIS PROBLEM BASED LEARNING TERINTEGRASI WORDWALL UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF SISWA - Sa'idah, Nisa Us; Handoyo, Eko; Supriyadi; Dirwanto; Akanto, Bara (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This research is research into the development of e-modules based on problem based learning integrated wordwall to improve students' cognitive abilities. The students' low scores on teaching materials for listening to sounds are due to the teaching materials being limited to textbooks and not taking advantage of technological developments. Teaching materials only consist of writing and pictures which are difficult for students to understand. This research aims to develop an e-module based on problem based learning to improve the cognitive abilities of fifth grade elementary school students. The type of research used is Research and Development with the ADDIE model (Analyze, Design, Development, implementation and Evaluation). The research subjects involved fifth grade students at SDN 02 Pekiringanalit. Data collection uses questionnaires and, pretest and posttest scores. Research data was analyzed using qualitative descriptive and quantitative descriptive methods. The results of the media expert validator are categorized as valid. The results of the material expert validator are categorized as very valid. And the response results from 20 fifth grade elementary school students were categorized as very valid. The overall results of the validator test are categorized as very valid so that the problem based learning integrated wordwall based e-module can be used for learning to hear because of sound in science lessons for class V elementary school.